Streptococcus Dysgalactiae Subspecies Equisimilis Endogenous Endophthalmitis Associated with Aortic Valve Abscess. (4th July 2019) - Gupta, Akash; Tsui, Edmund; Sarrafpour, Soshian; Lee, Carol M.; Modi, Yasha S.
ABSTRACT: Purpose : To describe a case of endogenous endophthalmitis from Streptococcus dysgalactiae subspecies equisimilis in the setting of an aortic valve abscess Methods : Retrospective case report. Results : A 72-year-old white male presented with fevers, encephalopathy, and decreased vision in his left eye. His visual acuity was 20/20 in his right eye and finger counting in the left eye. Workup revealed an aortic valve abscess. Examination of his left eye revealed dense anterior chamber fibrin and no view of the retina. B-scan ultrasonography revealed loculated hyperechoic areas consistent with vitreous inflammation. A vitreous tap and injections with vancomycin and ceftazidime were performed. Visual acuity worsened to no-light perception 5 days later. Vitreous and blood cultures grew Streptococcus dysgalactiae subspecies equisimilis . He received another intravitreal injection of vancomycin with no improvement. Conclusions: Streptococcus dysgalactiae subspecies equisimilis is an emerging pathogen and may cause severe intraocular infections with a poor visual outcome.